2018
DOI: 10.1182/blood-2017-09-808402
|View full text |Cite
|
Sign up to set email alerts
|

Five percent of healthy newborns have an ETV6-RUNX1 fusion as revealed by DNA-based GIPFEL screening

Abstract: 9. Zeidan AM, Sekeres MA, Garcia-Manero G, et al; MDS Clinical Research Consortium. Comparison of risk stratification tools in predicting outcomes of patients with higher-risk myelodysplastic syndromes treated with azanucleosides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
90
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 24 publications
5
90
0
1
Order By: Relevance
“…The presence of clone-specific mutations in patient neonatal blood spots has demonstrated a prenatal origin of most B-cell precursor ALL cases, namely those with high-hyperdiploidy or ETV6-RUNX1-translocation. Recently, it was suggested that up to 5% of all newborns harbor translocation ETV6-RUNX1 (30). In combination with a constitutively aberrant immune system, it is possible that children who develop B-cell precursor ALL were unable to eliminate these preleukemic cells, thus allowing transformation to leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of clone-specific mutations in patient neonatal blood spots has demonstrated a prenatal origin of most B-cell precursor ALL cases, namely those with high-hyperdiploidy or ETV6-RUNX1-translocation. Recently, it was suggested that up to 5% of all newborns harbor translocation ETV6-RUNX1 (30). In combination with a constitutively aberrant immune system, it is possible that children who develop B-cell precursor ALL were unable to eliminate these preleukemic cells, thus allowing transformation to leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…As secondary alterations are needed for most subtypes, these first hits produce a preleukemic state. The secondary mutations only occur in a fraction of carriers [6][7][8][9]. There is convincing evidence that a significant percentage of these preleukemic lesions can arise prenatally and transform after postnatal secondary events occur [6][7][8][9][10][11][12] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent “second‐hit” occurring postnatally in a population of “preleukemia” cells would initiate the final steps for leukemia to develop and manifest clinically. Interesting, the ETV6‐RUNX1 fusion has been detected in up to 5% of healthy newborn blood samples, as an example of a relatively high proportion of children potentially harboring a “first‐hit” preleukemia clone 4 …”
mentioning
confidence: 99%